Emerging Islamic Banks in the KSA: The Case Study of Alinma Bank - Mohamad, Khaliq Ahmad; Ahmed, Dirar Elmahi Elobeid (IIUM Journal of Case Studies in Management, 2021)
The main purpose of this case study is to specify the key factors that assist Alinma Bank in achieving its objectives and to ensure continuous business operations carried out by the bank in the event of a disaster. In addition, it discusses the fintech employed by the bank and the lessons learned from its experiences. Moreover, the case study highlights the role of the Shariah board in monitoring and supervising the banking products and services in accordance to Islamic principles.